Silver Nanowires: Aligning Ag Nanowires by a Facile Bioinspired Directional Liquid Transfer: Toward Anisotropic Flexible Conductive Electrodes (Adv. Mater. 25/2018). Issue 25 (15th June 2018) - Meng, Lili; Bian, Ruixin; Guo, Cheng; Xu, Bojie; Liu, Huan; Jiang, Lei
Abstract : Directional liquid transfer by a conical fiber array provides a facile and low‐cost approach to fabricate highly oriented AgNW‐based thin films by fine tuning the tri‐phase contact line during wetting and dewetting under directional stress. As described by Huan Liu and co‐workers in article number1706938, the as‐prepared transparent flexible electrodes (TFEs) show clear anisotropic conductivity with good bending stability and transparency.